(untitled) (International relations and international law Journal, 2018)
In the first decades of the 21 century the world community pays more and more attention to the solution of regional and global issues of energy security that identify the development of states, rates of their social, economic and political development. Along with the increase of the threats on global and regional levels, challenges of non-traditional and non-military character, and strengthening the interdependence of countries and regions, the process of drain on basic energy resources is taking place. Energy sector of Kazakhstan is one of the leading branches of social and economic life of the country. This article is focused on energy security as one of the core issues of national and economic security in the context of globalization. The essence of economic security and its main principles targeted at current sustainable and onward development of the Republic of Kazakhstan in the field of energy has been analyzed. Key worlds: Kazakhstan, Energy security, foreign policy sustainable development.